Method for directly recycling and regenerating waste positive electrode material through spontaneous lithiation and application
By generating pentoxy lithium solution through spontaneous lithiation, the high energy consumption and pollution problems in lithium-ion battery recycling are solved, and efficient replenishment of lithium ions and improvement of electrical performance is achieved, which is suitable for commercial production.
Patent Information
- Application Number
- CN202411687619.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-02-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing lithium-ion battery recycling technology has problems with high energy consumption and pollution, and lithium-ion inactivation has led to a decrease in battery cycle stability and a rapid decline in capacity.
By reacting LiOH with 1-pentanol to generate a pentoxy lithium solution, the thermodynamic barrier of the lithiation reaction in the waste cathode material is reduced, spontaneous lithiation is achieved, and the lithium ions consumed in the battery is supplemented.
It effectively improves the replenishment efficiency of lithium ions, reduces energy consumption and pollution, and has good electrical performance, which is suitable for commercial production.
Smart Images

Figure CN119481407A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of waste lithium-ion battery recycling, and in particular to a method and application for directly recycling and regenerating waste positive electrode materials through spontaneous lithiation. Background Art
[0002] With the rapid development of electric vehicles and energy storage devices, the use of lithium-ion batteries (LIBs) is booming, and the number of consumed LIBs is also increasing. Therefore, battery recycling has become one of the focuses of interest in both industry and academia. Currently, thermal and hydrometallurgical recovery methods are widely used to extract valuable lithium and transition metal elements from degraded batteries for reuse. However, the high-temperature smelting involved in the pyrometallurgical method and the strong acid leaching in the hydrometallurgical method have raised concerns about energy consumption and pollution. Therefore, the development of direct recovery of spent cathode materials can serve as a promising alternative.
[0003] As a highly-regarded energy storage technology, the recycling and reuse of positive electrode materials of lithium-ion batteries can greatly alleviate energy consumption. The key to the recycling of positive electrode materials is to re-adsorb lithium ions and replenish the consumption of lithium ions.
[0004] During the charging and discharging process of lithium-ion batteries, the material itself usually causes some lithium ions to be inactivated, which will damage the battery's cycle stability to a certain extent. As the number of cycles increases, the discharge capacitance and capacity will drop rapidly.
[0005] Therefore, in view of the shortcomings of the prior art, a method is provided to compensate for the deactivated lithium ions in the battery after the battery is cycled. Summary of the invention
[0006] The purpose of the present invention is to provide a method and application for directly recovering and regenerating waste positive electrode materials through spontaneous lithiation. Experiments have found that LiOH and 1-pentanol can react to generate a pentyl lithium solution. The chain structure of the pentyl lithium solution greatly reduces the adsorption energy on the surface of degraded NCM particles, thereby promoting the spontaneous lithiation of the waste positive electrode material system under environmental conditions. The present invention has low cost, is simple and reasonable, has good electrical properties, and is suitable for commercial production.
[0007] To achieve the above-mentioned purpose, the present invention provides a method for directly recovering and regenerating waste positive electrode materials by spontaneous lithiation, wherein pentyloxy lithium C5H 11 The self-adsorption function of OLi reduces the thermodynamic barrier of the lithiation reaction in the waste positive electrode material. In the absence of an external driving force, lithium pentoxide spontaneously adsorbs on the surface of the degraded cathode particles and spontaneously lithiates, thereby replenishing the lithium consumed in the waste batteries.
[0008] Preferably, the direct recycling method of waste positive electrode materials comprises the following steps: S1, disassembly process, the waste positive electrode material is NCM positive electrode material; S2, lithium pentoxide preparation process; S3, lithiation process.
[0009] Preferably, the method specifically comprises the following steps: (1) manually dismantling waste positive electrode materials to obtain degraded positive electrode materials, washing the dismantled positive electrode materials with NMP solution and 1M NaOH solution, and preparing the positive electrode materials into powder; removing polyvinylidene fluoride binder and electrolyte components with NMP solution, and removing residual aluminum impurities with NaOH solution; (2) Add LiOH to the n-pentanol solution, maintain the pH value of the mixed solution at 7-11, dissolve and react in the reactor, and stir continuously to ensure sufficient contact between LiOH and the n-pentanol solution. Repeat the above operation if necessary; the concentration of LiOH solution is 99%, and the concentration of n-pentanol solution is 95%.
[0010] (3) placing the powdered positive electrode material into a lithium pentoxide solution and stirring the solution to react, and separating the solid residue after the reaction is completed; (4) The solid residue is dried in a vacuum oven at 50-70°C and then sintered in a muffle furnace. The reaction temperature is gradually increased until the reaction is completed to obtain a regenerated positive electrode material and the temperature is kept to ensure the replenishment of lithium ions.
[0011] Preferably, in step (2), the reaction is carried out until the transparent solution turns light yellow, the dissolution reaction and stirring time are 10-14 hours, and the ratio of LiOH to n-pentanol solution is 1.5:1.
[0012] Preferably, the molar amount of the degraded positive electrode material input in step (3) is less than half of the molar amount of lithium in the lithium pentoxide solution, and the stirring time is 3-5 hours.
[0013] Preferably, in step (4), the temperature is raised twice in the muffle furnace, and Li2CO3 can be appropriately added before the temperature is raised. The initial temperature of the muffle furnace is 300-500°C, and the sintering is performed for 3 hours to decompose lithium pentoxide into Li2CO3, and then the temperature is raised to 600-800°C and sintered for 5 hours to decompose Li2CO3 into Li2O, and then the temperature is raised to 800-900°C and sintered for 3 hours to complete the repair process. Among them, the temperature of 300-500°C can ensure the fusion of the solid solution, 600-800°C can embed Li into the lattice, and 800-900°C ensures the sintering of the material.
[0014] Preferably, at the end of the reaction in step (4), an amorphous coating is present on the surface of the regenerated positive electrode material, and the coating disappears after being kept at 800-900° C. for 1 hour, and no new chemical bond is generated between the coating and the regenerated positive electrode material.
[0015] The present invention also provides an application of the above-mentioned method for directly recovering and regenerating waste positive electrode materials through spontaneous lithiation, which is applied to the recovery of waste positive electrode materials and the regenerated positive electrode materials, and the regenerated positive electrode materials are assembled into button batteries or soft packs.
[0016] Preferably, the steps of assembling the regenerated positive electrode material into a button battery are: A1. Mix the regenerated positive electrode material with acetylene black and PVD in a mass ratio of 8:1:1 and dissolve them in NMP solution to prepare a slurry; B1. Apply the slurry evenly on the surface of the aluminum foil. The loading density of the slurry on the surface of the aluminum foil is 5 mg cm -2 , and dried in a vacuum environment at 120°C to prepare the positive electrode. The positive electrode was cut into a disc with a diameter of 12 mm; C1. Use a metal lithium sheet as the negative electrode, polypropylene as the separator, ethyl carbonate, diethyl carbonate and dimethyl carbonate mixed in a mass ratio of 1:1:1 as the electrolyte, and assemble them with the positive electrode into a button battery.
[0017] Preferably, the steps of assembling the regenerated positive electrode material into a soft pack battery are: A2, mixing the regenerated positive electrode material with acetylene black and PVD in a mass ratio of 8:1:1, and dissolving them in NMP solution to prepare a slurry; B2. Apply the slurry evenly on the surface of the aluminum foil. The loading density of the slurry on the surface of the aluminum foil is 15 mg cm -2 , vacuum drying overnight in a vacuum environment at 120°C to prepare the positive electrode; C2, graphite is used as the negative electrode, polypropylene is used as the separator, and ethyl carbonate, diethyl carbonate and dimethyl carbonate are mixed in a mass ratio of 1:1:1 as the electrolyte. After cutting, the electrode sheets are stacked, and a soft-pack battery is obtained after injecting the electrolyte and packaging.
[0018] Therefore, the present invention adopts the above-mentioned method and application of direct recovery and regeneration of waste positive electrode materials through spontaneous lithiation, which has the following beneficial effects: 1. The adsorption energy of the lithium pentoxide solution generated by the present invention is higher than that of the LiOH solution, which solves the problem of the decrease in the capacity of the lithium ion battery caused by the deactivation of lithium ions inside the lithium ion battery and effectively improves the replenishment efficiency of lithium ions in the material; 2. The product generated by the lithium pentoxide prepared in the present invention after multiple heating can well enter the system gap of the waste positive electrode material to supplement the inactivated lithium ions; 3. The preparation method of the present invention is simple to operate, low in cost, and has high commercial application value.
[0019] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is a flow chart of a method for directly recovering and regenerating waste positive electrode materials through spontaneous lithiation and its application in the present invention; Figure 2 is the XRD diagram of the waste positive electrode material NCM622 disassembled in Example 1 of the present invention; Figure 3 This is the XRD diagram of the regenerated positive electrode material NCM622 after being soaked in lithium pentoxide in Example 1 of the present invention; Figure 4 This is the electrical performance diagram of the waste positive electrode material NCM622 disassembled in Example 1 of the present invention; Figure 5 This is the electrical performance diagram of NCM622 assembled with the regenerated positive electrode material in Example 1 of the present invention; Figure 6 This is the electrical performance diagram of NCM622 prepared by wet recovery of positive electrode materials in comparative example 1; Figure 7 This is the electrical performance diagram of NCM622 assembled with positive electrode material recycled by pyrolysis in Example 3. DETAILED DESCRIPTION
[0021] The technical solution of the present invention is further described below through the accompanying drawings and embodiments.
[0022] As the instruction manual Figure 1 As shown, the present invention provides a method for directly recovering and regenerating waste positive electrode materials through spontaneous lithiation, through pentyloxy lithium C5H 11 The self-adsorption function of OLi reduces the thermodynamic barrier of the lithiation reaction in the waste positive electrode material. In the absence of an external driving force, lithium pentoxide spontaneously adsorbs on the surface of the degraded cathode particles and spontaneously lithiates, thereby replenishing the lithium consumed in the waste batteries.
[0023] The direct recycling method of waste positive electrode materials includes the following steps: S1, disassembly process, the waste positive electrode material is NCM positive electrode material; S2, lithium pentoxide preparation process; S3, lithiation process.
[0024] The specific steps include: (1) manually dismantling waste positive electrode materials to obtain degraded positive electrode materials, washing the dismantled positive electrode materials with NMP solution and 1M NaOH solution, and preparing the positive electrode materials into powder; removing polyvinylidene fluoride binder and electrolyte components with NMP solution, and removing residual aluminum impurities with NaOH solution; (2) Add LiOH to the n-pentanol solution, maintain the pH value of the mixed solution at 7-11, dissolve and react in the reactor, and stir continuously to ensure sufficient contact between LiOH and the n-pentanol solution. Repeat the above operation if necessary; the concentration of LiOH solution is 99%, and the concentration of n-pentanol solution is 95%.
[0025] (3) placing the powdered positive electrode material into a lithium pentoxide solution and stirring the solution to react, and separating the solid residue after the reaction is completed; (4) The solid residue is dried in a vacuum oven at 50-70°C and then sintered in a muffle furnace. The reaction temperature is gradually increased until the reaction is completed to obtain a regenerated positive electrode material and the temperature is kept to ensure the replenishment of lithium ions.
[0026] In step (2), the reaction is carried out until the transparent solution turns light yellow, the dissolution reaction and stirring time are 10-14 hours, and the ratio of LiOH to n-pentanol solution is 1.5:1.
[0027] In step (3), the input molar number of the degraded positive electrode material is less than half of the molar number of lithium in the lithium pentoxide solution, and the stirring time is 3-5 hours.
[0028] In step (4), the temperature is raised twice in the muffle furnace, the initial temperature of the muffle furnace is 300-500°C, sintered for 3 hours, the lithium pentoxide is decomposed into Li2CO3, then the temperature is raised to 600-800°C, sintered for 5 hours, the Li2CO3 is decomposed into Li2O, during this process, Li2CO3 can be appropriately supplemented, and then the temperature is raised to 800-900°C, sintered for 3 hours, thereby completing the repair process. Among them, the temperature of 300-500°C can ensure the fusion of the solid solution, 600-800°C can embed Li into the lattice, and 800-900°C ensures the sintering of the material.
[0029] At the end of the reaction in step (4), an amorphous coating is present on the surface of the regenerated positive electrode material. The coating disappears after being kept at 800-900°C for 1 hour, and no new chemical bond is generated between the coating and the regenerated positive electrode material.
[0030] The present invention also provides an application of the above-mentioned method for directly recovering and regenerating waste positive electrode materials through spontaneous lithiation, which is applied to the recovery of waste positive electrode materials and the regenerated positive electrode materials, and the regenerated positive electrode materials are assembled into button batteries or soft-pack batteries.
[0031] Preferably, the steps of assembling the regenerated positive electrode material into a button battery are: A1. Mix the regenerated positive electrode material with acetylene black and PVD in a mass ratio of 8:1:1 and dissolve them in NMP solution to prepare a slurry; B1. Apply the slurry evenly on the surface of the aluminum foil. The loading density of the slurry on the surface of the aluminum foil is 5 mg cm -2, and dried in a vacuum environment at 120°C to prepare the positive electrode. The positive electrode was cut into a disc with a diameter of 12 mm; C1. Use a metal lithium sheet as the negative electrode, polypropylene as the separator, ethyl carbonate, diethyl carbonate and dimethyl carbonate mixed in a mass ratio of 1:1:1 as the electrolyte, and assemble them with the positive electrode into a button battery.
[0032] Preferably, the steps of assembling the regenerated positive electrode material into a soft pack battery are: A2, mixing the regenerated positive electrode material with acetylene black and PVD in a mass ratio of 8:1:1, and dissolving them in NMP solution to prepare a slurry; B2. Apply the slurry evenly on the surface of the aluminum foil. The loading density of the slurry on the surface of the aluminum foil is 15 mg cm -2 , vacuum drying overnight in a vacuum environment at 120°C to prepare the positive electrode; C2, graphite is used as the negative electrode, polypropylene is used as the separator, and ethyl carbonate, diethyl carbonate and dimethyl carbonate are mixed in a mass ratio of 1:1:1 as the electrolyte. After cutting, the electrode sheets are stacked, and a soft-pack battery is obtained after injecting the electrolyte and packaging.
[0033] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention. Any other changes, modifications, substitutions, combinations, and simplifications made without violating the spirit and principle of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention. In addition, it should be understood that after reading the contents of the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the claims attached to this application, and all belong to the scope of protection of the present invention.
[0034] Unless otherwise defined, the technical terms used in this document have the same meanings as those generally understood by those skilled in the art to which this application belongs; the use of relevant terms in this document is only for describing specific embodiments and is not intended to limit this application.
[0035] Unless otherwise specified in the present invention, the reagents, instruments, and equipment used are those commonly used by technicians in this field.
[0036] Example 1 The waste positive electrode material is selected from LiNi 0.6 Co 0.2 Mn 0.2 O2(NCM622), its XRD spectrum is as follows Figure 2 As shown, the direct recycling and regeneration method of waste positive electrode materials comprises the following steps: (1) Disassemble the waste NCM622 battery positive electrode material into powder to obtain degraded powdered NCM622 positive electrode material as a raw material for repair.
[0037] (2) Dissolve 6 mol of LiOH in 4 mol of 1-pentanol, stir continuously, and react overnight to form a lithium pentoxide solution.
[0038] (3) Then 20 g of degraded NCM622 powder was added to the solution and stirred for 4 h under ambient conditions.
[0039] (4) Separate the obtained powder and dry it in vacuum.
[0040] (5) It was mixed with 0.05 mol Li2CO3, heated at 300 °C for 3 h in a muffle furnace, then heated at 600 °C for 5 h, and then sintered at 850 °C for 3 h, and then cooled to room temperature to obtain regenerated NCM622.
[0041] Figure 3 It is the XRD spectrum of the regenerated positive electrode material NCM622 prepared in this embodiment, which proves that the material was prepared in this embodiment.
[0042] The regenerated positive electrode material, acetylene black and PVD were mixed in a mass ratio of 8:1:1 and dissolved in NMP solution to prepare a slurry. The slurry was evenly applied to the surface of the aluminum foil. The loading density of the slurry on the surface of the aluminum foil was 5 mg cm -2 , and dried in a vacuum environment at 120°C to prepare the positive electrode. The positive electrode was cut into a disc with a diameter of 12 mm; a metal lithium sheet was used as the negative electrode, polypropylene was used as the separator, and ethyl carbonate, diethyl carbonate and dimethyl carbonate were mixed in a mass ratio of 1:1:1 as the electrolyte, and assembled with the positive electrode into a button battery.
[0043] Example 2 The waste positive electrode material is selected from LiNi 0.5 Co 0.2 Mn 0.3 O2 (NCM523), a direct recovery and regeneration method of the positive electrode material through spontaneous lithiation, comprising the following steps: (1) Disassemble the waste NCM523 battery positive electrode material into powder to obtain degraded powdered NCM523 positive electrode material as a raw material for repair.
[0044] (2) Dissolve 6 mol of LiOH in 4 mol of 1-pentanol, stir continuously, and react overnight to form a lithium pentoxide solution.
[0045] (3) Then 20 g of degraded NCM622 powder was added to the solution and stirred for 4 h under ambient conditions.
[0046] (4) Separate the obtained powder and dry it in vacuum.
[0047] (5) It was mixed with 0.04 mol Li2CO3, heated at 300 °C for 3 h in a muffle furnace, then heated at 600 °C for 5 h, and then sintered at 850 °C for 3 h, and then cooled to room temperature to obtain regenerated NCM523.
[0048] (6) The regenerated NCM523 is placed in a NMP solution for a short cleaning and then dried.
[0049] (7) The recycled positive electrode material, acetylene black and PVD were mixed in a mass ratio of 8:1:1 and dissolved in NMP solution to prepare a slurry; the slurry was evenly applied to the surface of the aluminum foil. The loading density of the slurry on the surface of the aluminum foil was 5 mg cm -2 , and dried in a vacuum environment at 120°C to prepare the positive electrode. The positive electrode was cut into a disc with a diameter of 12 mm; a metal lithium sheet was used as the negative electrode, polypropylene was used as the separator, and ethyl carbonate, diethyl carbonate and dimethyl carbonate were mixed in a mass ratio of 1:1:1 as the electrolyte, and assembled with the positive electrode into a button battery.
[0050] Example 3 The waste positive electrode material is selected from LiNi 0.8 Co 0.2 Mn 0.2 O2 (NCM811), a direct recovery and regeneration method of the positive electrode material through spontaneous lithiation, comprising the following steps: (1) Disassemble the waste NCM811 battery positive electrode material into powder to obtain degraded powdered NCM811 positive electrode material as a raw material for repair.
[0051] (2) Dissolve 6 mol of LiOH in 4 mol of 1-pentanol, stir continuously, and react overnight to form a lithium pentoxide solution.
[0052] (3) Then 20 g of degraded NCM622 powder was added to the solution and stirred for 4 h under ambient conditions.
[0053] (4) Separate the obtained powder and dry it in vacuum.
[0054] (5) It was mixed with 0.04 mol Li2CO3, heated at 300 °C for 3 h in a muffle furnace, then heated at 600 °C for 5 h, and then sintered at 850 °C for 3 h, and then cooled to room temperature to obtain regenerated NCM811.
[0055] (6) The regenerated NCM811 is placed in NMP solution for a short cleaning and then dried.
[0056] (7) The recycled positive electrode material, acetylene black and PVD were mixed in a mass ratio of 8:1:1 and dissolved in NMP solution to prepare a slurry; the slurry was evenly applied to the surface of the aluminum foil. The loading density of the slurry on the surface of the aluminum foil was 5 mg cm -2 , and dried in a vacuum environment at 120°C to prepare the positive electrode. The positive electrode was cut into a disc with a diameter of 12 mm; a metal lithium sheet was used as the negative electrode, polypropylene was used as the separator, and ethyl carbonate, diethyl carbonate and dimethyl carbonate were mixed in a mass ratio of 1:1:1 as the electrolyte, and assembled with the positive electrode into a button battery.
[0057] Example 4 The regenerated NCM622 prepared in Example 1 was mixed with acetylene black and PVD in a mass ratio of 8:1:1, and dissolved in NMP solution to prepare a slurry; The slurry was evenly applied to the surface of the aluminum foil. The loading density of the slurry on the surface of the aluminum foil was 15 mg cm -2 , vacuum drying overnight in a vacuum environment at 120°C to prepare the positive electrode; Graphite is used as the negative electrode, polypropylene is used as the separator, and ethyl carbonate, diethyl carbonate and dimethyl carbonate are mixed in a mass ratio of 1:1:1 as the electrolyte. After cutting, the electrode sheets are stacked, and a soft-pack battery is obtained after injecting the electrolyte and packaging.
[0058] Comparative Example 1 Recycling NCM622 using wet method Step 1: Crushing: Wet crushing of waste lithium-ion batteries; Step 2, screening: the crushed material is screened with a 80-mesh standard sieve to separate the Cu, Al, and Fe shells from the cathode material; Step 3, selective ammonia leaching of valuable metals: after the cathode material is placed in a container, a ternary leaching agent is added; Step 4: Extraction of copper from ammonia leaching solution: Dissolve NiCl2·6H2O, CoCl2·6H2O, LiCl and CuCl2 in a ternary leaching agent to prepare solutions with concentrations of 0.5, 1, 1 and 1 g·L -1 The mixed solution of Li, Ni, Co and Cu was prepared. Then, the liquid phase and the organic phase were added to the container and mechanically stirred in a constant temperature water bath at a given temperature for a certain period of time to achieve extraction equilibrium. Then, Cu was extracted in the actual leaching solution. After extraction, various concentrations of sulfuric acid (0.3-2.4 mol·L) were used. -1 Stripping of Cu from the organic phase; Step 5: Regeneration of waste cathode material NCM622 by co-precipitation of raffinate: After copper extraction, NiCl2·6H2O and CoCl2·6H2O were added to regenerate Ni in the aqueous phase. 2+ and Co 2+ The molar ratio of was adjusted to 1:1, and the precursor NCM622 powder was obtained by reacting with NaOH in a constant temperature reactor at 55°C. The peristaltic pump was used to adjust the flow rate of the precipitant NaOH and the liquid phase rich in Ni and Co so that the pH of the system was accurately controlled at 11.25. After the reaction was completed, it was aged for more than 4 hours, and the obtained precursor was repeatedly washed with 60°C deionized water to neutrality and dried at 100°C to obtain a dry precursor NCM622 powder. 1 mol·L -1 Sodium carbonate, control flow rate at 1.5 mL min -1 The Li-rich raffinate was slowly added dropwise at 60°C to produce Li2CO3. After filtration, the precipitated Li2CO3 was washed several times and dried under vacuum at 85°C for later use. Step 6, synthesis of positive electrode material NCM622: The positive electrode material was prepared by a two-stage heating method. First, the molar ratio of the precursor NCM622 and Li2CO3 was controlled to be Li:Ni+Co=1.1:1. An appropriate amount of ethanol was first added to the planetary ball mill for wet mixing for 4 h. After the ethanol evaporated, it was dry mixed for 2 h to be fully mixed. Then, the mixture was placed in a muffle furnace in an oxygen atmosphere and heated at 3 °C·min -1 Heated to 550°C, kept constant for 5 hours, and further heated at 1°C min -1 Heating to 800°C and maintaining for 10 hours to obtain the positive electrode material NCM622; Step 7, preparation of electrode pole pieces: according to the ratio of positive electrode material: conductive agent: binder of 90:4:6, weigh a certain mass of binder into a container, add an appropriate amount of NMP, heat at 120℃ to dissolve naturally and stir, remove bubbles until colorless, transparent and uniform, accurately weigh an appropriate amount of positive electrode material and conductive agent and put them into an agate jar, add a ball mill and transfer the binder into the jar, wrap the lid with plastic wrap after stirring evenly, and use a ball mill at a suitable speed for 12 hours. The obtained viscous slurry is evenly coated on aluminum foil and placed in a 120℃ oven for drying to volatilize NMP to obtain pole pieces. In order to make the electrode material and aluminum foil tightly bonded, the dried electrode strips are rolled under a certain pressure, and finally punched into round pole pieces on a punching machine, and the masses are weighed and placed in a 60℃ vacuum drying oven for drying for standby use; Step 8, button cell assembly: button cells are assembled into half cells with lithium sheets as counter electrodes. All materials are vacuum dried and placed in a glove box. First, the negative electrode shell is placed, and then 2 drops of electrolyte are added after the lithium sheet is placed. A diaphragm is placed in the middle, and 1 to 2 drops of electrolyte are added again to fully wet the diaphragm. The positive electrode material is placed in the middle of the diaphragm, and then the gasket, spring, and positive electrode shell are placed in turn. A small manual sealing machine is used to seal the shell to obtain a finished button cell.
[0059] Comparative Example 2 Recycling NCM523 using wet method Step 1: Crushing: Wet crushing of waste lithium-ion batteries; Step 2, screening: the crushed material is screened with a 80-mesh standard sieve to separate the Cu, Al, and Fe shells from the cathode material; Step 3, selective ammonia leaching of valuable metals: after the cathode material is placed in a container, a ternary leaching agent is added; Step 4: Extraction of copper from ammonia leaching solution: Dissolve NiCl2·6H2O, CoCl2·6H2O, LiCl and CuCl2 in a ternary leaching agent to prepare solutions with concentrations of 0.5, 1, 1 and 1 g·L -1 The mixed solution of Li, Ni, Co and Cu was prepared. Then, the liquid phase and the organic phase were added to the container and mechanically stirred in a constant temperature water bath at a given temperature for a certain period of time to achieve extraction equilibrium. Then, Cu was extracted in the actual leaching solution. After extraction, various concentrations of sulfuric acid (0.3-2.4 mol·L) were used. -1 Stripping of Cu from the organic phase; Step 5: Regeneration of waste cathode material NCM523 by co-precipitation of raffinate: After copper extraction, NiCl2·6H2O and CoCl2·6H2O were added to regenerate Ni in the aqueous phase. 2+ and Co 2+ The molar ratio of was adjusted to 1:1, and the precursor NCM523 powder was obtained by reacting with NaOH in a constant temperature reactor at 55°C. The peristaltic pump was used to adjust the flow rate of the precipitant NaOH and the liquid phase rich in Ni and Co so that the pH of the system was accurately controlled at 11.25. After the reaction was completed, it was aged for more than 4 hours, and the obtained precursor was repeatedly washed with 60°C deionized water to neutrality and dried at 100°C to obtain a dry precursor NCM523 powder. 1 mol·L -1 Sodium carbonate, control flow rate at 1.5 mL min -1 The Li-rich raffinate was slowly added dropwise at 60°C to produce Li2CO3. After filtration, the precipitated Li2CO3 was washed several times and dried under vacuum at 85°C for later use. Step 6, synthesis of positive electrode material NCM523: The positive electrode material was prepared by a two-stage heating method. First, the molar ratio of the precursor NCM523 and Li2CO3 was controlled to be Li:Ni+Co=1.1:1. An appropriate amount of ethanol was first added to the planetary ball mill for wet mixing for 4 hours. After the ethanol evaporated, it was dry mixed for 2 hours to be fully mixed. Then, the mixture was placed in a muffle furnace in an oxygen atmosphere and heated at 3°C·min -1 Heated to 550°C, kept constant for 5 hours, and further heated at 1°C min -1 Heating to 800°C and maintaining for 10 hours to obtain the positive electrode material NCM523; Step 7, preparation of electrode pole pieces: according to the ratio of positive electrode material: conductive agent: binder of 90:4:6, weigh a certain mass of binder into a container, add an appropriate amount of NMP, heat at 120℃ to dissolve naturally and stir, remove bubbles until colorless, transparent and uniform, accurately weigh an appropriate amount of positive electrode material and conductive agent and put them into an agate jar, add a ball mill and transfer the binder into the jar, wrap the lid with plastic wrap after stirring evenly, and use a ball mill at a suitable speed for 12 hours. The obtained viscous slurry is evenly coated on aluminum foil and placed in a 120℃ oven for drying to volatilize NMP to obtain pole pieces. In order to make the electrode material and aluminum foil tightly bonded, the dried electrode strips are rolled under a certain pressure, and finally punched into round pole pieces on a punching machine, and the masses are weighed and placed in a 60℃ vacuum drying oven for drying for standby use; Step 8, button cell assembly: button cells are assembled into half cells with lithium sheets as counter electrodes. All materials are vacuum dried and placed in a glove box. First, the negative electrode shell is placed, and then 2 drops of electrolyte are added after the lithium sheet is placed. A diaphragm is placed in the middle, and 1 to 2 drops of electrolyte are added again to fully wet the diaphragm. The positive electrode material is placed in the middle of the diaphragm, and then the gasket, spring, and positive electrode shell are placed in turn. A small manual sealing machine is used to seal the shell to obtain a finished button cell.
[0060] Comparative Example 3 Lithium recovery from NCM622 using pyrometallurgy Step 1: Mix pyrometallurgical slag, water and hydrochloric acid to obtain a mixed acid material, wherein the mass ratio of slag: water: hydrochloric acid is 1: (0-2): (1-3), and the concentration of hydrochloric acid is 30wt%; Step 2: The mixed acid material is subjected to a heat-insulating reaction at a temperature of 15 to 85° C. for 2 to 4 hours, and the pH value at the end point of the reaction is controlled to be 2 to 3; Step 3: drying the mixed acid material after the reaction at 190-300° C. in vacuum to obtain an aluminum-removing material; Step 4: Soak the aluminum-removing material in water for 1 to 3 hours to obtain a leaching slurry; Step 5: performing solid-liquid separation on the leached slurry to obtain a leached liquid and a solid A; Step 6: adding lithium sulfate to the leaching solution, filtering, and obtaining a lithium chloride conversion solution and a solid B; Step 7: Separating lithium chloride from other divalent ions in the lithium chloride conversion solution to obtain a lithium chloride solution and a divalent ion salt solution; Step 8: preparing a lithium salt product from a lithium chloride solution; Step nine: using the obtained lithium salt product as a lithium source to prepare NCM positive electrode material, thereby packaging it with the negative electrode electrolyte to form a button battery.
[0061] Comparative Example 4 The waste positive electrode material used in this comparative example is LiNi 0.6 Co 0.2 Mn 0.2 O2 (NCM622), assembled into button batteries.
[0062] The batteries prepared in the above Examples 1-3 and Comparative Examples 1, 3, and 4 were subjected to electrochemical performance tests respectively. The electrochemical performance test results of the battery prepared in Example 1 are shown in the attached figure. Figure 5 The electrochemical performance test results of the battery prepared in Comparative Example 1 are shown in the attached Figure 6 The electrochemical performance test results of the battery prepared in Comparative Example 3 are shown in the attached Figure 7 The electrochemical performance test results of the battery prepared in Comparative Example 4 are shown in the attached Figure 4 As shown, the above results are summarized in Table 1: Table 1 Test data of multiple cycle capacity retention of battery positive electrode materials of Examples 1-3 and Comparative Examples 1, 3, and 4
[0063] It can be concluded from Table 1 that the regenerated positive electrode materials obtained in Examples 1, 2, and 3 were used as the positive electrode, and graphite was used as the negative electrode to assemble a button battery for charge and discharge comparison test. The capacitance retention rates after 100 cycles at a rate of 1C were 87.57%, 88.24%, and 89.35%, respectively, while those of Comparative Examples 1, 3, and 4 were only 79.00%, 75.87%, and 68.58%, respectively; thus, it can be seen that the cycle stability of the regenerated positive electrode material after lithium pentoxide adsorption is much higher than that of the regenerated positive electrode material prepared by the wet method and the fire method.
[0064] Therefore, the present invention adopts the above-mentioned method and application of direct recovery and regeneration of waste positive electrode materials through spontaneous lithiation. It is found through experiments that LiOH and 1-pentanol can react to generate a pentyl lithium solution. The chain structure of the pentyl lithium solution greatly reduces the adsorption energy on the surface of the degraded NCM particles, thereby promoting the spontaneous lithiation of the waste positive electrode material system under environmental conditions. The present invention has low cost, is simple and reasonable, has good electrical properties, and is suitable for commercial production.
[0065] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.
Claims
1. A method for directly recovering and regenerating waste positive electrode materials by spontaneous lithiation, characterized in that: By lithium pentoxide C5H 11 The self-adsorption function of OLi reduces the thermodynamic barrier of the lithiation reaction in the waste positive electrode material. In the absence of an external driving force, lithium pentoxide spontaneously adsorbs on the surface of the degraded cathode particles and spontaneously lithiates, thereby replenishing the lithium consumed in the waste batteries.
2. The method for directly recovering and regenerating waste positive electrode materials by spontaneous lithiation according to claim 1, characterized in that: The direct recycling method of waste positive electrode materials includes the following steps: S1, disassembly process, the waste positive electrode material is NCM positive electrode material; S2, lithium pentoxide preparation process; S3, lithiation process.
3. The method for directly recovering and regenerating waste positive electrode materials by spontaneous lithiation according to claim 2, characterized in that: The specific steps include: (1) manually disassembling the waste positive electrode material to obtain a degraded positive electrode material, washing the disassembled positive electrode material with an NMP solution and a 1M NaOH solution, and preparing the positive electrode material into a powder; (2) Add LiOH to the n-pentanol solution, maintain the pH value of the mixed solution at 7-11, dissolve and react in the reactor, and stir continuously to ensure sufficient contact between LiOH and the n-pentanol solution; (3) placing the powdered positive electrode material into a lithium pentoxide solution and stirring the solution to react, and separating the solid residue after the reaction is completed; (4) The solid residue is dried in a vacuum oven at 50-70°C and then sintered in a muffle furnace. The reaction temperature is gradually increased until the reaction is completed to obtain a regenerated positive electrode material and the temperature is kept to ensure the replenishment of lithium ions.
4. The method for directly recovering and regenerating waste positive electrode materials by spontaneous lithiation according to claim 3, characterized in that: In step (2), the reaction is carried out until the transparent solution turns light yellow, the dissolution reaction and stirring time are 10-14 hours, and the ratio of LiOH to n-pentanol solution is 1.5:
1.
5. The method for directly recovering and regenerating waste positive electrode materials by spontaneous lithiation according to claim 3, characterized in that: In step (3), the input molar number of the degraded positive electrode material is less than half of the molar number of lithium in the lithium pentoxide solution, and the stirring time is 3-5 hours.
6. The method for directly recovering and regenerating waste positive electrode materials by spontaneous lithiation according to claim 3, characterized in that: In step (4), the temperature is raised twice in the muffle furnace. The initial temperature of the muffle furnace is 300-500°C, and the sintering is performed for 3 hours to decompose the lithium pentoxide into Li2CO3. The temperature is then raised to 600-800°C and sintered for 5 hours to decompose Li2CO3 into Li2O. The temperature is then raised to 800-900°C and sintered for 3 hours to complete the repair process.
7. A method for directly recovering and regenerating waste positive electrode materials by spontaneous lithiation according to claim 6, characterized in that: At the end of the reaction in step (4), an amorphous coating is present on the surface of the regenerated positive electrode material, which disappears after being kept at 800-900°C for 1 hour.
8. An application of the method for direct recovery and regeneration of waste positive electrode materials by spontaneous lithiation as claimed in any one of claims 1 to 7, characterized in that: It is used for the recovery of waste positive electrode materials and the regeneration of positive electrode materials. The regenerated positive electrode materials are assembled into button batteries or soft-pack batteries.
9. The use of a method for directly recovering and regenerating waste positive electrode materials by spontaneous lithiation according to claim 8, characterized in that: The steps for assembling the recycled positive electrode material into a button battery are: A1. Mix the regenerated positive electrode material with acetylene black and PVD in a mass ratio of 8:1:1 and dissolve them in NMP solution to prepare a slurry; B1. Apply the slurry evenly on the surface of the aluminum foil. The loading density of the slurry on the surface of the aluminum foil is 5 mg cm -2 , and dried in a vacuum environment at 120°C to prepare the positive electrode. The positive electrode was cut into a disc with a diameter of 12 mm; C1. Use a metal lithium sheet as the negative electrode, polypropylene as the separator, ethyl carbonate, diethyl carbonate and dimethyl carbonate mixed in a mass ratio of 1:1:1 as the electrolyte, and assemble them with the positive electrode into a button battery.
10. The use of a method for directly recovering and regenerating waste positive electrode materials by spontaneous lithiation according to claim 8, characterized in that: The steps for assembling recycled positive electrode materials into soft pack batteries are as follows: A2, mixing the regenerated positive electrode material with acetylene black and PVD in a mass ratio of 8:1:1, and dissolving them in NMP solution to prepare a slurry; B2. Apply the slurry evenly on the surface of the aluminum foil. The loading density of the slurry on the surface of the aluminum foil is 15 mg cm -2 , vacuum drying overnight in a vacuum environment at 120°C to prepare the positive electrode; C2, graphite is used as the negative electrode, polypropylene is used as the separator, and ethyl carbonate, diethyl carbonate and dimethyl carbonate are mixed in a mass ratio of 1:1:1 as the electrolyte. After cutting, the electrode sheets are stacked, and a soft-pack battery is obtained after injecting the electrolyte and packaging.
Citation Information
Patent Citations
Method for recycling lithium ion positive electrode and recycled lithium ion positive electrode material
CN112271349A
Method for directly regenerating anode black powder of waste lithium ion battery and product
CN117712534A
Method of treating lithium battery to recycle its materials
EP1009058A1
Recycling and reconditioning of battery electrode materials
US9484606B1